2015
DOI: 10.14295/cs.v6i4.982
|View full text |Cite
|
Sign up to set email alerts
|

Interação salinidade da água de irrigação e substratos na produção de mudas de maracujazeiro amarelo

Abstract: RESUMO: A elevada taxa de evaporação e a limitação de água, em quantidade e qualidade principalmente nas áreas áridas e semiáridas, requerem a busca de estratégias que viabilizem a atividade agrícola. Com este trabalho objetivou-se avaliar a salinidade da água, o revestimento da cova e cálcio na produção e qualidade de maracujazeiro amarelo 'BRS Gigante Amarelo'. O experimento foi desenvolvido no município de Remígio-PB. Os tratamentos foram organizados em parcela subdividida 2A x (2R x 5Ca), correspondente a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 16 publications
2
19
0
9
Order By: Relevance
“…This reduction in passion fruit root growth with the increase in ECw can be attributed to the decrease in water absorption evidenced by the TWC and, therefore, it tends to affect the growth and development of the different plant parts, SDM ( Figure 4B) and RDM ( Figure 5A). Similar results were observed by Oliveira et al (2015) in P. edulis seedlings due to the increase in irrigation water salinity. These authors reported reductions of 65.8% in RDM as ECw increased from 0.3 to 3.5 dS m -1 .…”
Section: Figure 3 Stem Diameter -Sd (A) and Total Water Consumption supporting
confidence: 87%
See 2 more Smart Citations
“…This reduction in passion fruit root growth with the increase in ECw can be attributed to the decrease in water absorption evidenced by the TWC and, therefore, it tends to affect the growth and development of the different plant parts, SDM ( Figure 4B) and RDM ( Figure 5A). Similar results were observed by Oliveira et al (2015) in P. edulis seedlings due to the increase in irrigation water salinity. These authors reported reductions of 65.8% in RDM as ECw increased from 0.3 to 3.5 dS m -1 .…”
Section: Figure 3 Stem Diameter -Sd (A) and Total Water Consumption supporting
confidence: 87%
“…Based on the results of Figure 3A, there was a reduction of 2.64% in stem diameter per unit increase in water salinity, which corresponds to a decrease of 11.66% between plants irrigated with water of highest and lowest saline levels. This behavior is due to the reduction in the absorption of Oliveira et al (2015), who found reductions of 11.08% in the SD of P. edulis due to the increment in ECw from 0.3 to 3.5 dS m -1 . Figure 3B shows the linear reduction of 4.48% in the total water consumption per unit increase in the electrical conductivity of the irrigation water (ECw).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Oliveira et al (2015a) afirmam que a partir da condutividade elétrica de 1,5 dS m -1 o aumento da concentração de sais de sódio no substrato exerce fitotoxicidade às plantas de maracujazeiro desencadeando um conjunto de alterações iônicas e hormonais comprometendo o crescimento das plantas (SÁ et al, 2013).…”
Section: Resultsunclassified
“…However, works that seek the production of formulations of alternative substrates for the production of seedlings, seeking mitigation of the effect caused by the saline stress in the culture of the passion fruit plant are scarce (Oliveira et al, 2015), which it would be an alternative for the producer as cost reduction and use of salty water. In this context, it was aimed at with this work to evaluate the production of seedlings of yellow passion fruit plant submitted to different substrates and different saline waters.…”
mentioning
confidence: 99%